Ten-Year Review of The Bibliometry Network in Research on Micro, Small, and Medium Enterprises (MSMeS): 2011–2021 - Maydiantoro, Albet (Economic Education and Entrepreneurship Journal, 2024)
Recently, the attention of economists has been increasing toward MSMEs. However, no research analyzes bibliometrically to assess the development of the latest research trends in the MSME sector. To address this gap, this study reviewed 471 MSME studies published between 2011 and 2021 in the Scopus database using the PRISMA guidelines for review. This study uses descriptive and bibliometric analysis using VOSviewer software to answer four research problems: the total volume and geographic distribution of the study; most influential writers; the most influential sources of journals, books, and conferences; and recent topics. The results showed that India and Indonesia were the most productive countries, followed by the US, Mexico, and Spain. The leading writer is Kharub, M. (India), and the most influential writer is Singh, M.P. (India), which contributes to MSME Research. The largest source is the Journal of Physics Conference Series (Conference and Proceeding), and the most influential sources are Resources, Conservation, and Recycling (journal). The topics that emerged the most were MSMEs, Small and Medium Enterprises, Micro, and India. Meanwhile, trending topics related to MSMEs are COVID-19, MSME performance, fintech, and technology adoption. This paper is expected to contribute to research related to MSMEs and can help researchers to develop further scientific research themes. This paper is also expected to be the basis of a country's government policy in developing MSMEs to strengthen the national economy. The researchers suggest a further review of MSMEs in the future more specifically in one continent, region, or country.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.202-214